2021
DOI: 10.3390/biology10010027
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiovascular Therapeutic Potential of Propolis—A Comprehensive Review

Abstract: Owing to its chemical richness, propolis has a myriad of therapeutic properties. To the authors’ knowledge, this is the first comprehensive review paper on propolis to focus exclusively on its major effects for cardiovascular health. The propolis compound varieties with the most promising therapeutic benefits and their respective physiological mechanisms will be discussed. Propolis displays an anti-atherosclerotic activity, attained through modulation of the plasma lipid profile and through stabilization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 140 publications
0
25
0
Order By: Relevance
“…Plant-derived natural medicine is a vital health resource with various applications, including heart disorder prevention and management [ 143 ]. Plants are the major sources of the continuous need for new drugs with lesser side effects and lower costs [ 188 ]. Hence, there is an urgent interest in safe, effective, green, and more economical drug candidates [ 189 ].…”
Section: Plant-derived Commercial Drugs For Heart Diseasesmentioning
confidence: 99%
“…Plant-derived natural medicine is a vital health resource with various applications, including heart disorder prevention and management [ 143 ]. Plants are the major sources of the continuous need for new drugs with lesser side effects and lower costs [ 188 ]. Hence, there is an urgent interest in safe, effective, green, and more economical drug candidates [ 189 ].…”
Section: Plant-derived Commercial Drugs For Heart Diseasesmentioning
confidence: 99%
“…A recent clinical study involving nearly 1000 subjects revealed that the increases in the levels of Hct, Hb, and RBC within the normal ranges were beneficial for the maintenance of vascular function and structure, which may decrease the risk of cardiovascular disease [ 47 ]. Propolis has been extensively studied for its cardiovascular therapeutic potential [ 48 ]. A randomized clinical trial on healthy subjects showed that orally administered propolis supplement resulted in a significant decrease in BP after two months [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of recent studies are reporting new physiological effects on neurodegenerative diseases, such as Parkinson's disease, 56−58 and on cardiovascular disease. 59 Several reviews on the beneficial effects of propolis against COVID-19 have been published. 60−62 Recently, clinical trial reports suggest that propolis might contribute to ameliorating the symptoms and reducing the negative effects of COVID-19.…”
Section: Antiobesity and Antidiabetes Effects Of Propolismentioning
confidence: 99%
“…Propolis has long been known to have various biological activities. An increasing number of recent studies are reporting new physiological effects on neurodegenerative diseases, such as Parkinson’s disease, and on cardiovascular disease . Several reviews on the beneficial effects of propolis against COVID-19 have been published. Recently, clinical trial reports suggest that propolis might contribute to ameliorating the symptoms and reducing the negative effects of COVID-19. , However, much remains unclear on this topic and more studies need to be conducted to obtain further clinical evidence.…”
Section: Antiobesity and Antidiabetes Effects Of Propolismentioning
confidence: 99%